2017
DOI: 10.5194/acp-17-7365-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparing parameterized versus measured microphysical properties of tropical convective cloud bases during the ACRIDICON–CHUVA campaign

Abstract: Abstract. The objective of this study is to validate parameterizations that were recently developed for satellite retrievals of cloud condensation nuclei supersaturation spectra, N CCN (S), at cloud base alongside more traditional parameterizations connecting N CCN (S) with cloud base updrafts and drop concentrations. This was based on the HALO aircraft measurements during the ACRIDICON-CHUVA campaign over the Amazon region, which took place in September 2014. The properties of convective clouds were measured … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 59 publications
5
66
1
Order By: Relevance
“…As noted by Molleker et al (2014), the CDP uncertainty is approximately 10 %. Braga et al (2017) performed a comparison between the CDP and the other HALO cloud probes and concluded that they agree within instrumental uncertainties. The vertical wind component (w) was measured by the Basic HALO Measurement and Sensor System (BAHAMAS) located at the nose of the aircraft and calibrated according to Mallaun et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Molleker et al (2014), the CDP uncertainty is approximately 10 %. Braga et al (2017) performed a comparison between the CDP and the other HALO cloud probes and concluded that they agree within instrumental uncertainties. The vertical wind component (w) was measured by the Basic HALO Measurement and Sensor System (BAHAMAS) located at the nose of the aircraft and calibrated according to Mallaun et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Cecchini et al (2017a) have also demonstrated that a 100 % increase in aerosol concentrations led to an 84 % increase in the concentration of droplets, but the same relative increase in vertical velocity corresponded only to a 43 % change. Braga et al (2017) have compared HALO microphysical probe measurements of cloud droplet concentrations with a parameterization based on CCN and updraft at the cloud base. Jäkel et al (2017) have presented a new methodology to retrieve the vertical distribution of the hydrometeor phase using cloud-side reflected solar radiation measurements and have discussed the mixed-phase layer as a function of aerosol loading.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
“…In terms of sources and conditions, the ATTO and ZF2 sites are comparable (C. Pöhlker et al, 2017). The cCO data include ATTO site measurements from 2012 to 2017.…”
Section: Seasonal Cycles Of Remote Sensing and In Situ Datamentioning
confidence: 99%
“…Briefly: The BT analysis is based on the hybrid single particle Lagrangian integrated trajectory model (HYSPLIT, NOAA-ARL) with meteorological input data from the global data assimilation system (GDAS1) (Draxler and Hess, 1998 in reddish colors; and (iv) a group of 'inland' trajectories in east-southeasterly (ESE) directions including clusters ESE1, ESE2, and ESE3 as well as one cluster towards the south-west (i.e., SW1). For a detailed characterization of the region, which is covered by the BTs and represents the ATTO site footprint with the trace gas, aerosol, and CCN sources that are presumably most relevant for the long-term observation at the ATTO site, we refer the reader to C. Pöhlker et al (2017).…”
Section: Backward Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation